2020
DOI: 10.1177/1934578x20919545
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effects of Gyrophoric Acid on UVA-Irradiated Normal Human Dermal Fibroblasts

Abstract: This research was conducted to identify the anti-aging effects of gyrophoric acid on the skin, using normal human dermal fibroblasts. The anti-aging effects of gyrophoric acid on dermal fibroblasts were demonstrated through cell viability, verification of collagen, type I, alpha 1 (COL1A1)/COL3A1/matrix metalloproteinases 1 (MMP1) messenger ribonucleic acid (mRNA) expression levels with quantitative real-time reverse-transcription polymerase chain reaction, and protein estimation using type I collagen/MMP1-enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, gyrophoric acid exerted a photoprotective effect on HaCaT cells with a sun protection factor (SPF) of (SPF > 5) [ 120 , 121 ]. Anti-aging effects were also investigated on ultraviolet A (UVA)-treated dermal fibroblasts, showing upregulated mRNA levels of COL1A1/COL3A1/SOD2 genes and type I collagen protein levels [ 122 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…Moreover, gyrophoric acid exerted a photoprotective effect on HaCaT cells with a sun protection factor (SPF) of (SPF > 5) [ 120 , 121 ]. Anti-aging effects were also investigated on ultraviolet A (UVA)-treated dermal fibroblasts, showing upregulated mRNA levels of COL1A1/COL3A1/SOD2 genes and type I collagen protein levels [ 122 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…Besides this, GA has been proven to have potent anti-aging effects. According to Shim (2020) , GA prevented skin aging in normal HDF cells exposed to UV-A radiation. Even after the HDF tissue had been exposed to UV-A, GA increased the mRNA level of specific collagen-encoding genes.…”
Section: Pharmacological Importance Of Tridepsidesmentioning
confidence: 99%
“…These are associated with the production of type I collagen, which also increases with gyrophoric acid treatment. In addition, it was found that it also decreased the expression of matrix metalloproteinases, proteins that degrade mature collagen molecules during the aging process [ 74 ].…”
Section: Lichen Species Of Pharmaceutical Interestmentioning
confidence: 99%